Exploration Of Ethnomathematics At Sipamutung Temple In Siparau Village - Siregar, Hanif Luthfi; Ahmad Rifki Alparwis; Anestasya Amanda; Elvi Mailani; Mardhiyah Kharismayanda (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This research aims to identify and interpret the mathematical elements found in the architecture of Sipamutung Temple in Siparau village. The background of this problem focuses on the importance of understanding the relationship between culture and mathematics, especially in the context of local cultural heritage. The method used in this research is ethnography with a descriptive approach, which includes observation, documentation, and literature exploration. The results showed that the floor plan of Sipamutung Temple was designed with various complexities that reflect the level of mathematical development of the local community. The research uncovered the concept of flat shapes such as square, rectangle and trapezoid in the temple structure, as well as the application of geometry principles in its design. The conclusion of this study emphasizes the importance of appreciating the sociocultural relevance of mathematics and practices in local cultures, as well as the need for efforts to preserve existing cultural heritage. It is hoped that the results of this research can provide the community with a better understanding of the mathematical concepts contained in Sipamutung Temple and increase awareness of the cultural values that exist around it